2014
DOI: 10.2147/mder.s51426
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive imaging of microcirculation: a technology review

Abstract: Microcirculation plays a crucial role in physiological processes of tissue oxygenation and nutritional exchange. Measurement of microcirculation can be applied on many organs in various pathologies. In this paper we aim to review the technique of non-invasive methods for imaging of the microcirculation. Methods covered are: videomicroscopy techniques, laser Doppler perfusion imaging, and laser speckle contrast imaging. Videomicroscopy techniques, such as orthogonal polarization spectral imaging and sidestream … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 63 publications
0
53
0
3
Order By: Relevance
“…Microcirculatory assessment by sidestream dark-field imaging presented in this review exhibited heterogeneous effects in different tissues in one study [68], but no improvement in another [51]. Comparisons of different microcirculatory imaging techniques have been reported in literature [41, 74–76]. Investigators who conducted a comparative study on cochlear blood flow concluded that intravital microscopic measurements were more sensitive than laser Doppler measurements [77].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microcirculatory assessment by sidestream dark-field imaging presented in this review exhibited heterogeneous effects in different tissues in one study [68], but no improvement in another [51]. Comparisons of different microcirculatory imaging techniques have been reported in literature [41, 74–76]. Investigators who conducted a comparative study on cochlear blood flow concluded that intravital microscopic measurements were more sensitive than laser Doppler measurements [77].…”
Section: Discussionmentioning
confidence: 99%
“…We considered some of these, including videomicroscopic techniques, whilst offering direct visualization of the microcirculation, the tissue contact element is largely uncontrolled and may cause pressure-induced artefacts. On the other hand, laser techniques are susceptible to motion artefacts, so that combining techniques might enhance the accuracy of microcirculatory assessments [76]. Only one study presented in this review used a combination of techniques to assess the microcirculation (i.e., laser Doppler flowmetry and sidestream dark-field imaging) and reported persistent acidosis, microcirculatory and mitochondrial dysfunction despite resuscitation with hydroxyethyl starch (HES) fluid [15].…”
Section: Discussionmentioning
confidence: 99%
“…Capillary video microscopy is an optical imaging technique that uses green-spectrum light to illuminate superficial micro vessels in the nail beds. Detectors capture backscattered light and images are reconstructed producing images of capillaries 52 . Contrast-enhanced ultrasound can be used to quantify microvascular recruitment in deeper tissues, like skeletal muscle.…”
Section: Microcirculationmentioning
confidence: 99%
“…К методам исследования микроциркуляции бульбар-ной конъюнктивы глаза относятся: биомикроскопия, фо-тографирование и кинематография микрососудов конъ-юнктивы, телевизионная биомикроскопия микрососудов глаза [2], флюоресцентная ангиография переднего отрез-ка глаза [7], лазерная спекл-контрастная визуализация [8], ортогональная поляризация спектральных изображе-ний [9], боковая темнопольная визуализация [10], ком-пьютерная телевизионная микроскопия [11], лазерная допплеровская флоуметрия [12], измерение диаметра конъюнктивальных сосудов с помощью Retinal Vessel Analyzer (RVA, Imedos, Германия) [13].…”
Section: методы исследования бульбарной конъюнктивыunclassified
“…Методы чувствительны к артефактам движения и не учи-тывают гетерогенность кровотока, основного параметра микроциркуляции. Для выражения результатов использу-ются относительные единицы [10,17]. Лазерная доппле-ровская флоуметрия является неинвазивным методом определения микроциркуляции, в том числе и кожной [18].…”
Section: методы исследования бульбарной конъюнктивыunclassified